Worldview and Conservation: Crocodiles and Caimans in the Pijao Indigenous People in Colombia - Edison D. Bonilla-Liberato; Nelson Martínez-Criollo; Islena Villalba-Yate (Ethnobiology Letters, 2025)
Sacred and cultural practices that link biodiversity with Indigenous communities play a vital role in conservation. Likewise, fauna associated with these practices have positive implications for many species with which they share their ecosystems. Recognizing how cultural worldviews shape, and are shaped by, the physical characteristics of a territory can strengthen conservation and restoration efforts. However, in the case of the Pijao people, an Indigenous group from Colombia, socioeconomic and landscape transformations have deeply affected cultural practices and identity, putting at risk both ancestral knowledge and the species that benefit from it. We report on the connection between the Pijao people with two species of crocodylians (Crocodylus acutus and Caiman crocodilus) as well as the role these animals play within their worldview and ancestral medicine. Our study offers new contributions to the cultural and spiritual role of crocodilians in Colombia. It highlights the importance of strengthening Indigenous knowledge and identity to maintain customs and traditions, as preserving these ancestral practices is essential for the continuity of ethnic identity and the protection of these species as a unique expression of cultural heritage.